Environmental Triggers of lrgA Expression in Streptococcus mutans - Ishkov, Ivan P.; Ahn, Sang-Joon; Rice, Kelly C.; Hagen, Stephen J. (Frontiers in Microbiology, 2020)
The cidAB and lrgAB operons of Streptococcus mutans encode proteins that are structurally similar to the bacteriophage lambda family of holin-antiholin proteins, which are believed to facilitate cell death in other bacterial species. Although their precise function is not known, cidAB and lrgAB are linked to multiple virulence traits of S. mutans, including oxidative stress tolerance, biofilm formation, and autolysis. Here we investigate the regulation of lrgAB which in S. mutans shows a complex dependence on growth conditions that is not fully understood. By combining single-cell imaging of a fluorescent gene reporter with microfluidic control of the extracellular environment, we identify specific environmental cues that trigger lrgA expression and characterize cell-to-cell heterogeneity in lrgA activity. We find that the very abrupt activation of lrgA at stationary phase is tightly synchronized across the population. This activation is controlled by a small number of inputs that are sensitive to growth phase: extracellular pyruvate, glucose, and molecular oxygen. Activation of lrgA appears to be self-limiting, so that strong expression of lrgA is confined to a short interval of time. lrgA is programmed to switch on briefly at the end of exponential growth, as glucose and molecular oxygen are exhausted and extracellular pyruvate is available. Our findings are consistent with studies of other bacteria showing that homologs of lrgAB participate, with input from lytST, in the reimport of pyruvate for anaerobic fermentative growth.